Study of Electrical Conductivity of Epoxy/Graphene Platelet Nanocomposites - Yu, Shuaibo (Université d'Ottawa / University of Ottawa, 2014)
Polymer nanocomposites are prepared by appropriately dispersing nanoscale fillers into polymer matrices. Graphene, a two-dimensional nano-carbon material with outstanding physical properties, has been widely studied as a conductive filler for nanocomposites. In this work, a gum Arabic aqueous solution was proposed as a new media to exfoliate graphite into few-layer graphene by liquid-phase sonication. Successful exfoliation was confirmed by Raman spectroscopy, scanning electron microscopy and transmission electron microscopy. Four types of graphene nanoplatelets were used to study the effects of the filler's aspect ratio. The one with the largest aspect ratio showed the best performance, where the conductivity of neat epoxy was increased by five orders of magnitude at 10 wt.%. Using a hot sonication technique and adding a small amount of second fillers further improved the electrical conductivities. The highest conductivity obtained in this study was 0.025 S/cm, which met the requirements of electromagnetic shielding material.
Keywords: Graphene; Nanocomposite; Electrical conductivity